2012
DOI: 10.2308/bria-50151
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Feedback, Incentives, and Performance: Evidence from a Relatively Complex Forecasting Task

Abstract: This study extends prior research by examining a fairly common sequence of business events: numeric outcome information is produced and reviewed, decisions are influenced by this information, and the process repeats (i.e., a feedback loop occurs). We find that incentivized decision makers exhibit substantial decision improvement after only one iteration of summary outcome feedback. In contrast, other between-subjects groups fail to improve performance across iterations of Luft and Shields' (2001) forecasting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…In this study, two articles that used external contingency were found, namely Buchheit et al (2012) and Dekker et al (2012). Buchheit et al (2012) examined environmental uncertainty, which include volatility, complexity and strategic relation related to outcome feedback and incentive towards performance improvements. The result suggested that financial incentives and outcome feedback are both critical to performance improvement in relatively environmental uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, two articles that used external contingency were found, namely Buchheit et al (2012) and Dekker et al (2012). Buchheit et al (2012) examined environmental uncertainty, which include volatility, complexity and strategic relation related to outcome feedback and incentive towards performance improvements. The result suggested that financial incentives and outcome feedback are both critical to performance improvement in relatively environmental uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of studies that studied individual factors, namely Buchheit et al (2012) examined individual factors such as motivation, commitment and attitude related to the relation between outcome feedback and incentive towards performance improvements. The result suggested that financial incentives and outcome feedback are both critical to performance improvement in relatively individual factors.…”
Section: Resultsmentioning
confidence: 99%
“…(Herrera and Sanchez-Gonzalez, 2012;Oh et al, 2014). (Buchheit et al, 2012;Martins and Lopes, 2016).…”
Section: Conclusion Research Contribution and Directions For Future Researchmentioning
confidence: 99%
“…There is an implicit assumption that the link between rewards and performance is based on a mechanism by which rewards increase effort, which in turn improves performance (Bonner & Sprinkle, 2002;Buchheit et al, 2012). But, what counts as reliable metrics of cognitive effort is by no means settled (for discussion see Bonner and Sprinkle, 2002).…”
Section: The Role Of Rewards In Judgment and Decision-makingmentioning
confidence: 99%
“…This is often referred to as the crowding out effect (Deci, 1976;Frey, 1997;Lepper & Greene, 2015). Moreover, there is evidence to suggest that monetary incentives alone are not sufficient, and need to be presented in combination with output feedback in order to improve decision-making performance (Buchheit et al, 2012). To complement this, an association has been made between monetary rewards and expertise such that the greater the skill required to perform the decision-making task accurately the less likely financial incentives positively impact on performance (Vera-Munoz, 1998).…”
Section: The Role Of Rewards In Judgment and Decision-makingmentioning
confidence: 99%